Response of turmeric (Curcuma Zonga L.) to nitrogen in relation to application of farm yard manure and straw mulch - SINGH, B S GILL, R S RANDHAWA, G S RANDHAWA, J (Journal of Spices and Aromatic Crops, 1999)
Experiments were conducted during kharif 1995 and 1996 at Ludhiana, India, to study the response of turmeric (Curcuma longa) to nitrogen in relation to application of farm yard manure and wheat straw mulch. The treatments consisted of two levels of mulch (0 and 6 tJha), four levels of farmyard manure, (0, 20, 40 and 60 tJha) and three levels of nitrogen (0, 60 and 120 kg/ha). The study revealed that application of wheat straw mulch improved growth and yield of turmeric significantly. Rhizome yield increased significantly with each increase in farm yard manure level during 1996 with a maximum yield of 365.4 q/ha with 60 tJha of farm yard manure. Nitrogen levels did not affect growth and yield of turmeric significantly.